MECHANICAL PROPERTIES CHARACTERIZATION OF THE FRICTION WELDING OF ALUMUNIUM WITH COPPER USING VARIATIONS IN ROTATIONAL SPEED AND CONTACT SURFACE ROUGHNESS - Saefuloh, Iman; Sunardi, Sunardi; Lusiani, Rina; Jannah, Miftahul; Suryana, Suryana (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
One of the welding used for different materials is by using friction welding. Friction welding is a welding method by swiping the two materials until they reach some of the melting points of the materials to be joined and then subjected to constant pressure. In this study, the materials to be joined were aluminum and copper. By using variations of rotational speed and contact surface roughness, the mechanical properties of the welds were investigated. The speed variations used were 1230, 1500, and 2500 rpm. Meanwhile, for variations in surface roughness, sandpaper grades 100, 800, and 1500 were used. The results of this study were that at a rotational speed of 1230 rpm, the highest tensile strength and hardness values were obtained, namely 59.6 MPa and 54.6 HVN (Al), 112.1 HVN (Cu). For variations in surface roughness, the highest hardness value was found in surface roughness using sandpaper grade 1500, namely 54.18HVN (Al), and 112.1HVN (Cu). And the highest tensile strength is obtained on grade 100 sandpaper with a value of 52.48MPa. The results of the microstructure test in the weld joint area with a magnification of 1000x showed that the welding of aluminum and copper using the friction welding method was successful, as evidenced by the diffusion of aluminum and copper in this area.